Экология пестряка окончатого (Diptera, Tabanidae) - Бошко, Г.В. (Вестник зоологии, 1968)
Ch. italicus is one of the numerous Mediterranean species of horseflies throughout the Azov—Black Sea coast of the Ukraine. The highest activity of its attacks is observed on sandy spits, islands, estuary and salt lake coast in the period from the 20th of May up to the middle of August. The following conditions are optimal for Ch. italicus flight: temperature of the air — 27-30° C, its relative humidity — 80-95 p. c., illumina-tion — 10 000 lx and absence of wind. The larvae of all the ages tolerate very high ge-neral salinity of water surpassing 200°/00. On the Azov — Black Sea coast of the Ukraine the development of one generation of Ch. italicus lasts for one year. Mating and oviposition take place in June — July, the larva phase lasts for 11-13 months, and the puppa one — 10-20 days. Eclosion of the imago begins when the sum of effective tem-peratures reaches about 150° C.